1999
DOI: 10.1038/sj.bjc.6690734
|View full text |Cite
|
Sign up to set email alerts
|

Esthesioneuroblastoma is not a member of the primitive peripheral neuroectodermal tumour-Ewing’s group

Abstract: Esthesioneuroblastoma (ENB) is a rare malignant tumour thought to derive from neuroendocrine cells of the olfactory epithelium on the basis of location, morphologic, immunophenotypic and ultrastructural features. In fact, well differentiated ENB is characterized by the presence of neuropil, Homer Wright and olfactory rosettes (Hyams et al, 1988), by a positive immunoreactivity for neuron-specific enolase, synaptophysin, chromogranin and neurofilaments and, ultrastructurally, by cytoplasmic processes, microtubu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 32 publications
0
16
0
2
Order By: Relevance
“…Following the results from a recent study by Logsdon et al [26] [14] comprises the olfactory neuroblastoma (esthesioneuroblastoma; ICD-O 9522/3). This tumor is of olfactory membrane origin and probably does not belong to the peripheral neuroectodermal tumor-Ewing's tumor, as 2 recent molecular biological studies have demonstrated [28,29]. Characteristically, this tumor has a lobular structure with well-defined groups of neuroblasts and neurofibrils separated by highly vascular fibrous stroma.…”
Section: Classificationmentioning
confidence: 98%
“…Following the results from a recent study by Logsdon et al [26] [14] comprises the olfactory neuroblastoma (esthesioneuroblastoma; ICD-O 9522/3). This tumor is of olfactory membrane origin and probably does not belong to the peripheral neuroectodermal tumor-Ewing's tumor, as 2 recent molecular biological studies have demonstrated [28,29]. Characteristically, this tumor has a lobular structure with well-defined groups of neuroblasts and neurofibrils separated by highly vascular fibrous stroma.…”
Section: Classificationmentioning
confidence: 98%
“…However, no statistically significant survival difference was found for these variables. Most ONBs do not exhibit balanced translocations and the presence of fusion genes in patient samples and cell lines [49, 50]. Early research improperly suggested ONB exhibiting a translocation (11;22)(q24;q12) and producing an EWS/FLI1 transcript, which might cause misclassification to primitive neuroectodermal tumors (PNETs) [51, 52].…”
Section: Cytogenetic Alterationsmentioning
confidence: 99%
“…89 Studies with fluorescence in situ hybridisation 39,40 and RT-PCR 31,40 have not confirmed this translocation in ENB. ENB should therefore be seen as a distinct entity from PNET and the Ewing's sarcoma family of tumours.…”
Section: Originmentioning
confidence: 99%
“…These were supplemented by another 19 relevant publications found in references cited. 4,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] The studies were divided into three types, according to their principal objectives: origin and aetiology of ENB, 9,11,15,[17][18][19]21,24,[27][28][29][30][31][32][33][34][35][36][37][38][39][40] histopathological diagnosis; 10,[12][13][14]23,37,[41][42][43][44]…”
Section: Search Strategy and Selection Criteriamentioning
confidence: 99%